2017
DOI: 10.1039/c7dt02243c
|View full text |Cite
|
Sign up to set email alerts
|

Terminal vs. bridging coordination of CO and NO ligands after decarbonylation of [W2Cp2(μ-PR2)(CO)3(NO)] complexes (R = Ph, Cy). An experimental and computational study

Abstract: Compounds [MCp(μ-PPh)(CO)(NO)] (M = Mo, W) were prepared by reacting the corresponding radicals [MCp(μ-PPh)(CO)] with NO, and displayed a terminal, linear NO ligand arranged cis to the P-donor ligand (Mo-Mo = 3.1400(7) Å). The related PCy-bridged complex [WCp(μ-PCy)(CO)(NO)] was prepared in a one-pot, three step procedure first involving deprotonation of the hydride complex [WCp(μ-H)(μ-PCy)(CO)] with K[BH(sec-Bu)], then oxidation of the resulting salt K[WCp(μ-PCy)(CO)] with [FeCp]BF at 243 K, and eventually by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Such behavior contrasts with the previously observed formation of a 1-hydrophosphinine-1-oxide ligand in the similar compound [CpFe(η 5 -2,4,6-triphenyl-1-hydrophosphinine-1-oxide)] (310). 279 Furthermore, reaction between complex 308 and [Cp 2 Fe]-PF 6 afforded the neutral dimer [Cp*Fe(η 5 -2,4,6-triphenylphosphinine)] 2 (311), which was then further oxidized using I 2 (1 equiv), to yield the cationic iron(II) compound [Cp*Fe(η 6 -2,4,6-triphenylphosphinine)]I (312, Scheme 39). Complex 312 can also be obtained by direct oxidation of 308 with I 2 .…”
Section: Metallocene Anionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such behavior contrasts with the previously observed formation of a 1-hydrophosphinine-1-oxide ligand in the similar compound [CpFe(η 5 -2,4,6-triphenyl-1-hydrophosphinine-1-oxide)] (310). 279 Furthermore, reaction between complex 308 and [Cp 2 Fe]-PF 6 afforded the neutral dimer [Cp*Fe(η 5 -2,4,6-triphenylphosphinine)] 2 (311), which was then further oxidized using I 2 (1 equiv), to yield the cationic iron(II) compound [Cp*Fe(η 6 -2,4,6-triphenylphosphinine)]I (312, Scheme 39). Complex 312 can also be obtained by direct oxidation of 308 with I 2 .…”
Section: Metallocene Anionsmentioning
confidence: 99%
“…The reactivity of 366 toward Brønsted acids, [AuCl­{P­( p -tol) 3 }], and elemental sulfur was explored, revealing that compound 366 displays a considerable metal-based nucleophilicity. This feature makes 366 an attractive precursor for the preparation of several ditungsten nitrosyl derivatives and the subsequent study of nitric oxide activation. …”
Section: Synthesis and Basic Reactivity Patterns Of D-block Metalatesmentioning
confidence: 99%
“…The molecule of 6 in the crystal (Figure 5 and 33 In order to achieve a 18electron configuration at each metal centre, an asymmetric coordination of the phosphanyl ligand (WPR 2 →Co) might be proposed for 6, which should be reflected in the observation of a shorter PCo length, even after allowing for the lower size of the Co atom. However, the WP and CoP lengths only differ from each other by some 0.22 Å, while the covalent radii of these metal atoms differ by some 0.35 Å.…”
Section: Structure Of the Wco Complexmentioning
confidence: 99%
“…An X-ray study revealed that the latter displays the unusual linear κ:η bridging mode (type D ), with it being strongly bound to one metal via the nitrogen atom [W2–N3 = 1.823(4) Å], while π binding the second metal atom through its N–O bond [W1–N3 = 2.191(4) Å; W1–O3 = 2.138(3) Å], which then becomes significantly elongated [N3–O3 = 1.271(5) Å] and presumably debilitated, in agreement with its very low N–O stretching frequency (1366 cm –1 ). The coordination mode of the NO ligand found in compound 5 was relatively unexpected because previous DFT studies on the decarbonylation products of the neutral complexes [W 2 Cp 2 (μ-PCy 2 )­(CO) 3 (NO)] revealed that carbonyl is a better-suited ligand than NO for bridging two metal atoms in a linear κ:η fashion . In fact, density functional theory (DFT) calculations on the cation in 5 (Figure ) and some possible isomers revealed that a linear κ:η-CO-bridged isomer would have the lowest energy, with the actual ordering found, when the nature and coordination mode of the bridging ligand are changed, being μ-κ:η-CO (0) < μ-κ:η-NO (+16) < μ-NO (+62) (relative Gibbs free energies at 298 K in kJ/mol; see the SI).…”
mentioning
confidence: 92%
“…The coordination mode of the NO ligand found in compound 5 was relatively unexpected because previous DFT studies on the decarbonylation products of the neutral complexes [W 2 Cp 2 (μ-PCy 2 )(CO) 3 (NO)] revealed that carbonyl is a better-suited ligand than NO for bridging two metal atoms in a linear κ:η fashion. 14 In fact, density functional theory (DFT) calculations on the cation in 5 ( Figure 1 ) and some possible isomers revealed that a linear κ:η-CO-bridged isomer would have the lowest energy, with the actual ordering found, when the nature and coordination mode of the bridging ligand are changed, being μ-κ:η-CO (0) < μ-κ:η-NO (+16) < μ-NO (+62) (relative Gibbs free energies at 298 K in kJ/mol; see the SI ). Therefore, we conclude that 5 is a kinetic product.…”
mentioning
confidence: 99%